Pengaruh Transformational Leadership Terhadap Work Engagement Di Lembaga Pemasyarakatan Kelas IIA Karawang - Nina Dayana; Padmono Wibowo (International Forum of Researchers and Lecturers, 2023)
This research was carried out to ascertain and evaluate the impact of transformational leadership on Work engagement in Lembaga Pemasyarakatan Kelas IIA Karawang, This study's methodology is quantitative. The participants in this study are was all employees in Lembaga Pemasyarakatan Kelas IIA Karawang as many as 50 people while 30 persons made up the study's sample. In In this research, a questionnaire used as a method of data collecting. The data collection approach used in this study used a questionnaire. The statistical tests used Validity, reliability, and normality tests were utilized in this investigation Tests, Linear Regression Analysis, Linearity Tests, and Linear Correlation Analysis, as well as IBM was used to process data for this investigation SPSS statistical software program Version 23, The outcome of this research prove the intensity of work engagement is influenced by transformational leadership Lembaga Pemasyarakatan Class IIA Karawang is 99% whereas other factors affect the remaining components